Treatment of the acute severe pulmonary embolism using endovascular methods - Keussen, Inger E. (Pol J Radiol, 2018)
PURPOSE: To present a single-centre experience with endovascular treatment of patients with severe symptoms secondary to acute pulmonary embolism (PE). MATERIAL AND METHODS: Twenty-five patients were treated due to contraindications or deficient effects of systemic thrombolytic therapy. The patients were treated with a combination of fragmentation and aspiration, only aspiration, or only fragmentation, and with catheter-directed thrombolytic therapy. RESULTS: The saturation was improved following treatment in all patients, except in one where the procedure could not be completed. There were no immediate or late procedure-related complications. CONCLUSIONS: Endovascular treatment of severe PE is a safe and efficient option in patients with failing effect or contraindication to systemic thrombolysis.